Iran Economic Monitor, Fall 2018 : Weathering Economic Challenges - World Bank Group (World Bank, Washington, DC, 2018)
Iranʼs GDP growth in 2017/18 eased considerably as the effect of large surge in oil revenues in the previous year dissipated. After undergoing an oil-based bounce in the economy in 2016/17, the economy registered a 3.8 percent growth in 2017/18 with the overwhelming majority of growth coming from the non-oil sectors. More than half of the growth can be attributed to services which grew by 4.4 percent. Oil, agriculture and services sectors are now back above the levels of activity they were prior to sanctions in 2012. But there was not a strong bounce back in the past two years for key sectors such as construction and trade, restaurant and hotel services following the stagnation in growth during the period of sanctions. The oil and gas sector witnessed a growth of 0.9 percent.Limited by the (Organization of the Petroleum Exporting Countries) OPEC quota for the agreed period, increasing production capacity or maintaining current production levels in the coming years would require a substantial increase in investments in the sector. However, the reintroduction of sanctions on the oil and gas sector in November 2018 by the United States (US) will mean the issue of export payments rather than investment needs will come to the fore.